2016
DOI: 10.1016/j.jpeds.2016.03.069
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes Measurement Information System in Children with Crohn's Disease

Abstract: Objectives To assess the criterion validity and responsiveness of Patient Reported Outcomes Measurement Information System (PROMIS) in a web-based cohort of children with Crohn’s disease. Study design We recruited children, ages 9 to 17, with Crohn’s disease and their parents from the web-based Crohn’s and Colitis Foundation of America Kids & Teens Study cohort. Upon entry into the cohort and 6 months later, children self-reported Crohn’s disease activity, health-related quality of life and PROMIS domains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…Mean age was 14.3 (based on 25 studies that reported a mean age). Three studies included only patients with CD . In the remaining studies that reported disease type, 67.1% had CD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mean age was 14.3 (based on 25 studies that reported a mean age). Three studies included only patients with CD . In the remaining studies that reported disease type, 67.1% had CD.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in 23 out of 28 studies, clinical disease activity was measured for CD, with the following indices: Paediatric Crohn's Disease Activity Index (PCDAI), short‐PCDAI abbreviated PCDAI, Harvey Bradshaw Index, Physician Global Assessment (PGA), (part of) Children's Somatisation Inventory, IBD‐symptom questionnaire, and Short‐Crohn's Disease Activity Index . Twenty‐five studies included UC patients and in 21 disease activity was measured using the following indices; Paediatric Ulcerative Colitis Activity Index (PUCAI), Physician Global Assessment, (part of) Children's Somatisation Inventory, IBD‐symptom questionnaire, Clinical score of Kozarek, Lichtiger Colitis Activity index, and PCDAI .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing interest in defining family-centered and parent-reported outcomes in fetal, 27 infant, 28 and childhood 29 conditions. The themes from this study suggest we should build on these efforts to define and measure family-centered outcomes in neonatal encephalopathy.…”
Section: Discussionmentioning
confidence: 99%